Cyber-attack and reliability monitoring of the synchrophasor smart grid network - Yadav, Atul Kumar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The recent advancement of synchrophasor measurements technology in the conventional power grid can monitor and control the state variables of the network very accurately at a high sampling rate in real-time. The complete observability of system states can be achieved through the Phasor Measurement Unit (PMU). The inclusion of a zero injection bus (ZIB) optimized the total number of PMU requirements for complete observation of the synchrophasor network. The communication channels between measurement devices and control centers are highly vulnerable to cyber threats. Thus, an anomaly that occurs with PMU devices during a cyber-attack can affect the system’s reliability. Therefore, monitoring the reliability of the synchrophasor network has become essential for healthy power operation. Synchrophasor measurement technology can enhance wide-area surveillance and security functionality. However, the dependability of such technologies in the context of information network accessibility has yet to be investigated in a coherent model. Growing electric grid defence levels to mitigate the impact of cyber-attacks is essential. The cumulative effect of synchrophasor network observability and reliability is discussed in this paper by optimizing the number of PMUs deployed and the interruption load that occurs during an anomaly with PMU while taking ZIB into account.The backup PMU deployment modeling is also presented to secure the reliability and observability of the grid network during an anomaly occurs with PMU. The indices, Interrupted Load Probability Index (ILPI) and Expected Demand Not Supplied (EDNS), are used to evaluate the reliability of synchrophasor grid networks by integrating the state probability of PMU unavailability due to cyber intrusion.